The Role of Philanthropic Communication in Transformative Da'wah - Paraswati , Vellyana; Ulya Faza Adilah, Siti (Ath Thariq Jurnal Dakwah dan Komunikasi, 2025)
This study examines the role of Islamic philanthropic institutions in promoting transformative da’wah, which integrates spiritual teachings with socio-economic empowerment. Using a mixed-methods approach, it combines qualitative case studies and quantitative data to strengthen analysis and validity. Data were collected through participant observation, in-depth and structured interviews, and document analysis. The research focuses on two West Java-based organizations: Baitulmaal Muamalat (BMM) and Inisiatif Zakat Indonesia (IZI), exploring how they manage ZISWAF (Zakat, Infaq, Sadaqah, and Waqf) to enhance community welfare. Findings show that IZI’s programs achieve high impact, with an average score of 4.32 out of 5, demonstrating alignment with transformative da’wah principles. BMM effectively leverages corporate social responsibility (CSR) partnerships to support initiatives such as Rumah Quran, integrated farming, and healthcare for marginalized groups, earning a solid score of 3.90. The study concludes that Islamic philanthropic organizations serve as key agents of structural change, translating Islamic values into sustainable, faith-based development models that promote social justice and community resilience.